Performance of the Department of Agriculture Horticulture and Livestock Service Office in Developing Farmer Groups in Kowioha Village Wundulako District Kolaka Regency - Pasla, Aldi; Said, Achmad Lamo; Mulku Zahari, Ahmad Farouq (Perkembangan Kajian Sosial, 2024)
The purpose of this study was to determine the performance of the Kolaka District Agriculture, Horticulture and Livestock Service Office in training farmer groups in Kowioha Village, Wundulako Subdistrict, Kolaka District. The research used descriptive qualitative techniques. The research location was Kowioha Village, Wundulako Subdistrict, Kolaka District. Informants included employees of the Kolaka Regency Agriculture and Horticulture Office, agricultural extension workers, Kowioha village officials, farmer group leaders, and the community as a farmer group. Data were sourced from primary and secondary data. Data collection techniques included observation, interviews, and documentation studies. After that, the data was analyzed using data analysis techniques including data collection, reduction, data presentation, and verification or conclusion drawing. The results showed that; 1) The productivity of agricultural extension workers' performance has not been carried out optimally in terms of carrying out the mentoring program to the farmer group community. 2) The quality of service has been going well, but needs to be improved, especially in providing information to each member of the farmer group. 3) The responsiveness of extension workers to the needs of farmer group communities is not optimal, such as the lack of certainty in the timing of providing seeds and fertilizers and the number of seeds provided is not in accordance with the number of members of the farmer group gapoktan, so that only some farmer community groups get it. 4) Responsibility has been well implemented. 5) The accountability of extension workers in improving the performance of coaching and development of farmer groups is quite good, although in its implementation there are still some obstacles.